Progress in improving the protection of species and habitats in Australia. (August 2016) - Barr, Lissa M.; Watson, James E.M.; Possingham, Hugh P.; Iwamura, Takuya; Fuller, Richard A.
Abstract: Historically, protected areas were often designated using criteria other than biodiversity conservation as the primary objective. With the emergence of the science of systematic conservation planning, the designation of new protected areas is increasingly made with explicit conservation objectives in mind. However, assessments of the performance of protected area systems typically include all protected areas, regardless of when they were designated, potentially obscuring recent improvements in conservation planning decisions. Thus, it is often unclear to what extent systematic conservation planning principles have influenced the placement of new protected areas. Here, we compare recently designated protected areas in Australia with the protected area system that existed prior to the introduction of systematic conservation planning guidelines in 2000. We ask whether there is a difference between past and recent protection in terms of (i) the size and spatial distribution of protected areas, (ii) the characteristics of broad regions in which protection is concentrated, and (iii) the extent to which protected areas represent ecosystems and threatened species in comparison with selecting protected areas at random. We find that the protected area system was historically biased toward areas with steep slopes and low human populations. In contrast, recent protection is more likely to be allocated to regions with high human population and high numbers of threatened species; we show that this effect is not simply a result of biases in the places now available for conservation. Despite this successful realignment of practice, we find that the increase in protected area coverage in poorly protected regions has occurred more slowly than expected if protected area selections were fully guided by systematic conservation planning principles. Our results demonstrate rapid progress in improving Australia's protected area system in the last decade, and highlight the importance of separating recent from historical additions to the protected area system when measuring the performance of conservation decision-making. Highlights: From 1999, Australia used conservation planning principles to guide new protection. This mandates protection of threatened species and ecologically distinct bioregions. Protection since 2000 was indeed more likely in regions with many threatened species. However, significant gaps in bioregional representation remain. This suggests partially successful implementation of protected area policy.